Pengaruh Model Pembelajaran Inkuiri Terbimbing Dengan Penggunaan Media Scarpbook Terhadap Motivasi Siswa Pada Pembelajaran IPAS Kelas IV UPTD SD Inpres Naikoten 1 - Kapi, Maria Yustania; Taty R. Koroh; Kurniayu T. R. A. Ratu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The study entitled “The Effect of the Guided Inquiry Learning Model with the Use of Scrapbook Media on Students’ Learning Motivation in IPAS Learning for Grade IV at UPTD SD Inpres Naikoten 1” was motivated by the low learning motivation of students, which had an impact on the less optimal learning outcomes. This condition was reflected in the low level of student involvement in the learning process and learning outcomes that had not yet reached the predetermined mastery criteria. This study aimed to determine the effect of the guided inquiry learning method assisted by scrapbook media on improving students’ learning motivation. The study employed a quantitative approach with a pre-experimental one-group pretest–posttest design. The subjects of the study were 14 students. Data collection techniques included observation, learning motivation questionnaires administered before and after the treatment, and documentation study. The data were analyzed using a paired sample t-test. The results of the analysis showed an increase in students’ learning motivation after the treatment, with a mean difference value of −20.714. The statistical test results showed a Sig. (2-tailed) value of 0.002 (< 0.05), indicating that there was a significant difference in learning motivation before and after the treatment. Therefore, the use of learning media implemented in this study proved to be effective in improving students’ learning motivation.